Experimental Study on Tele-Manipulation Assistance Technique Using a Touch Screen for Underwater Cable Maintenance Tasks - Gun Rae Cho; Geonhui Ki; Mun-Jik Lee; Hyungjoo Kang; Min-Gyu Kim; Ji-Hong Li (Journal of Marine Science and Engineering, 2021)
In underwater environments restricted from human access, many intervention tasks are performed by using robotic systems like underwater manipulators. Commonly, the robotic systems are tele-operated from operating ships; the operation is apt to be inefficient because of restricted underwater information and complex operation methods. In this paper, an assistance technique for tele-manipulation is investigated and evaluated experimentally. The key idea behind the assistance technique is to operate the manipulator by touching several points on the camera images. To implement the idea, the position estimation technique utilizing the touch inputs is investigated. The assistance technique is simple but significantly helpful to increase temporal efficiency of tele-manipulation for underwater tasks. Using URI-T, a cable burying ROV (Remotely Operated Vehicle) developed in Korea, the performance of the proposed assistance technique is verified. The underwater cable gripping task, one of the cable maintenance tasks carried out by the cable burying ROV, is employed for the performance evaluation, and the experimental results are analyzed statistically. The results show that the assistance technique can improve the efficiency of the tele-manipulation considerably in comparison with the conventional tele-operation method.